Network disruption detected in KZ (Kazakhstan) - Voidly (2026)
CRITICAL severity mixed detected in Kazakhstan. Confidence: 70%. Data sourced from IODA, CensoredPlanet.
Censorship Incident ID: KZ-2026-0004
Keywords: censorship; KZ; mixed; critical